Multisystem proteinopathy due to a homozygous p.Arg159His VCP mutation: A tale of the unexpected. (25th February 2020) - De Ridder, Willem; Azmi, Abdelkrim; Clemen, Christoph S.; Eichinger, Ludwig; Hofmann, Andreas; Schröder, Rolf; Johnson, Katherine; Töpf, Ana; Straub, Volker; De Jonghe, Peter; Maudsley, Stuart; De Bleecker, Jan L.; et al.
Abstract : Objective: To assess the clinical, radiologic, myopathologic, and proteomic findings in a patient manifesting a multisystem proteinopathy due to a homozygous valosin-containing protein gene ( VCP ) mutation previously reported to be pathogenic in the heterozygous state. Methods: We studied a 36-year-old male index patient and his father, both presenting with progressive limb-girdle weakness. Muscle involvement was assessed by MRI and muscle biopsies. We performed whole-exome sequencing and Sanger sequencing for segregation analysis of the identified p.Arg159His VCP mutation. To dissect biological disease signatures, we applied state-of-the-art quantitative proteomics on muscle tissue of the index case, his father, 3 additional patients with VCP -related myopathy, and 3 control individuals. Results: The index patient, homozygous for the known p.Arg159His mutation in VCP, manifested a typical VCP -related myopathy phenotype, although with a markedly high creatine kinase value and a relatively early disease onset, and Paget disease of bone. The father exhibited a myopathy phenotype and discrete parkinsonism, and multiple deceased family members on the maternal side of the pedigree displayed a dementia, parkinsonism, or myopathy phenotype. Bioinformatic analysis of quantitative proteomic data revealed the degenerative nature of the disease, with evidence suggesting selective failure of muscle regeneration and stress granule dyshomeostasis. Conclusion: We report a patient showing a multisystem proteinopathy due to a homozygous VCP mutation. The patient manifests a severe phenotype, yet fundamental disease characteristics are preserved. Proteomic findings provide further insights into VCP -related pathomechanisms.